(untitled) (Anclajes, 2012)
The Independence Wars established a strategic alliance in all ¨Hispanoamérica¨ –more symbolic than social or military– between Creole insurgents and indigenous peoples, which purpose would be to legitimize the warlike conflict against Spain. In the middle of the century, when the State-Nation projects began to be designed for expansion and territorial occupation, the indigenous populations were reconsidered by the Creole imaginary; this time; however, not as political subjects of a potential coalition but as heirs of a highly respected linguistic code. This work proposes to investigate the literate construction of such heritages in a series of texts that, by combining Romanticism and Scientism, shaped the aim of such exploration in South-America.